2011
DOI: 10.1097/aln.0b013e318201c88c
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen–activated Protein Kinase Activation by Nerve Growth Factor in Primary Sensory Neurons Upregulates μ-Opioid Receptors to Enhance Opioid Responsiveness Toward Better Pain Control

Abstract: Background: Sensory neuron opioid receptors are targets for spinal, epidural, and peripheral opioid application. Although local nerve growth factor (NGF) has been identified as a mediator of sensory neuron -opioid receptor (MOR) up-regulation, the signaling pathways involved have not been yet identified. Methods: Wistar rats were treated with intraplantar vehicle, Freund's complete adjuvant, NGF, NGF plus intrathecal p38 mitogen-activated protein kinase (MAPK) inhibitors, or NGF plus extracellular signal-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…ERK activation was observed in the perycaria of small primary afferent neurons (Donnerer et al 2005;Noguchi et al 2004;Obata et al 2003, although it also occurred in the peripheral processes of these cells (Aley et al 2001;Averill et al 2001;Dai et al 2002). Interestingly, pERK levels were found to be increased in primary afferents following exposure to nerve growth factor (NGF) (Amaya et al 2009;Averill et al 2001;Yamdeu et al 2011). ERK activation has also been shown to be responsible for the up-regulation of the brain-derived neurotrophic factor (BDNF) in the cell bodies of DRG neurons in models of peripheral inflammation and neuropathic pain (Obata et al 2003.…”
Section: Discussionmentioning
confidence: 93%
“…ERK activation was observed in the perycaria of small primary afferent neurons (Donnerer et al 2005;Noguchi et al 2004;Obata et al 2003, although it also occurred in the peripheral processes of these cells (Aley et al 2001;Averill et al 2001;Dai et al 2002). Interestingly, pERK levels were found to be increased in primary afferents following exposure to nerve growth factor (NGF) (Amaya et al 2009;Averill et al 2001;Yamdeu et al 2011). ERK activation has also been shown to be responsible for the up-regulation of the brain-derived neurotrophic factor (BDNF) in the cell bodies of DRG neurons in models of peripheral inflammation and neuropathic pain (Obata et al 2003.…”
Section: Discussionmentioning
confidence: 93%
“…Mechanical pain thresholds were assessed by a paw pressure algesiometer before (baseline) and after intraplantar injections of the opioid agonist fentanyl (0.5–1.25 μg/100 μL) as previously described (11,17). Paw pressure thresholds (PPT) were expressed as raw data in grams or as percent maximum possible effect according to the following equation: (PPT postinjection – PPT basal ) / (140 cut-off – PPT basal ) to correct for differences in baseline and to set the data in relation to the maximal effect of control animals.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent in vivo study, nerve growth factor was shown to increase the number of phosphorylated p38 MAPK immunoreactive neurons expressing MOR in dorsal root ganglia, increase peripherally directed axonal transport of MOR, and increase significant potentiation, as well as enhance efficacy in fentanyl- and buprenorphine-induced dose-dependent antinociception [48]. The expression of MOR gene in P19 cells by protein synthesis inhibitors is mediated through the activation of the PI-3K and p38 MAPK pathways, and inhibiting p38 MAPK decreases the constitutively expressed MOR expression levels in NMB neuroblastoma cells [20].…”
Section: Discussionmentioning
confidence: 99%